2020
DOI: 10.1186/s12864-020-07001-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of five poultry strains elucidates phylogenetic relationships and divergence in virulence genes in Morganella morganii

Abstract: Background: M. morganii is a bacterium frequently associated with urinary infections in humans. While many human strains are sequenced, only the genomes of few poultry strains are available. Here, we performed a detailed characterization of five highly resistant Morganella morganii strains isolated in association with Escherichia coli from diseased domestic Austrian poultry flocks, namely geese, turkeys and chicken layers. Additionally, we sequenced the genomes of these strains by NGS and analyzed phylogenetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…There are few reports on characterizing ARGs in individual Morganella isolates or a small collection of Morganella isolates ( n ≤ 22 in each study) ( 31 33 ). This study provides a genomic and bioinformatics view of the classification and evolution of Morganella species and the global prevalence of AGEs and associated ARGs in Morganella , based on a collection of 166 sequenced isolates, including 60 sequenced in this study.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on characterizing ARGs in individual Morganella isolates or a small collection of Morganella isolates ( n ≤ 22 in each study) ( 31 33 ). This study provides a genomic and bioinformatics view of the classification and evolution of Morganella species and the global prevalence of AGEs and associated ARGs in Morganella , based on a collection of 166 sequenced isolates, including 60 sequenced in this study.…”
Section: Discussionmentioning
confidence: 99%
“…genomes retrieved from GenBank and the cheese isolates confirm that M. morganii and M. psychrotolerans can be distinguished using genomic analysis. Palmieri et al (2020) showed that the trehalose operon negative (subsp. morganii ) and the trehalose operon positive (subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of more Morganella species would also explain why the trehalose operon positive H1R strain does not cluster together with the other subsp. sibonii strains ( Palmieri et al, 2020 ). DNA-DNA hybridization experiments of Emborg et al (2006) also revealed that two trehalose positive strains analyzed in their study did not group together with the strains from subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis of rRNA has been used for example for species identification of Campylobacter jejuni and Campylobacter coli [93], or Avibacterium paragallinarum [94]. NGS/WGS proved valuable in gaining more data regarding characterization of Morganella morganii [95], Ornithobacterium rhinotracheale [96], E. coli [97] and Salmonella Infantis [98]. These methods can also be applied for direct identification of bacterial communities as shown for samples from poultry carcasses in slaughterhouses [99].…”
Section: Bacteriologymentioning
confidence: 99%